The Influence of Dediphobia on Early Classroom Management in the Context of Islamic Religious Education - Ulpa Nurjanah Ulpa; Astuti Darmiyanti Astuti (Cv. Kayaswara, Indonesia, 2025)
Effective character education for elementary school children focuses on intrinsic motivation rather than external fear. The phenomenon of